2016
DOI: 10.1016/s1473-3099(16)30120-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and immunogenicity of the human papillomavirus 16/18 AS04-adjuvanted vaccine in women older than 25 years: 7-year follow-up of the phase 3, double-blind, randomised controlled VIVIANE study

Abstract: GlaxoSmithKline Biologicals SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(132 citation statements)
references
References 35 publications
2
125
0
1
Order By: Relevance
“…Second, 7-year follow-up data of Vaccine Immunogenicity and Efficacy (VIVIANE) study [40], a phase III, double-blind, randomized controlled trial of HPV 16/18 vaccine in women >25 years, were reported in The Lancet Infectious Diseases in 2016 [41]. In this study, a total of 5,747 women was in the vaccinated cohort (n=2,877 vaccine and n=2,870 control) and 4,407 were in the according-to-protocol cohort for efficacy (n=2,209 vaccine and n=2,198 control).…”
Section: Cervical Cancermentioning
confidence: 99%
“…Second, 7-year follow-up data of Vaccine Immunogenicity and Efficacy (VIVIANE) study [40], a phase III, double-blind, randomized controlled trial of HPV 16/18 vaccine in women >25 years, were reported in The Lancet Infectious Diseases in 2016 [41]. In this study, a total of 5,747 women was in the vaccinated cohort (n=2,877 vaccine and n=2,870 control) and 4,407 were in the according-to-protocol cohort for efficacy (n=2,209 vaccine and n=2,198 control).…”
Section: Cervical Cancermentioning
confidence: 99%
“…However, current data reveals high rates of immunogenicity and adequate duration of protection without any need for a booster dose. The 7-year follow-up of the VIVIANE study revealed that HPV 16-18 vaccine is still successful in protecting women older than 25 years against infections, cytological abnormalities, and lesions associated with HPV 16-18 as well as HPV 31 and HPV 45 (20).…”
Section: Efficacy and Safetymentioning
confidence: 99%
“…The HPV‐FASTER protocol, as proposed by an international group including many European countries, Australia and Mexico, aims to address this disconnection by combining both strategies with the ultimate purpose of accelerating the reduction in cervical cancer incidence and related mortality. Their proposal is based on the consistent results of previously describe primary HPV screening trials as well as with results from phase III trials comparing HPV vaccination against placebo among adult women (up to 55 years of age) . Their proposal includes HPV vaccination to women in a broad age range of 9–45 years, irrespective of HPV status and HPV‐based screening.…”
Section: Introductionmentioning
confidence: 98%